2009
DOI: 10.1007/s12650-009-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of transient interfacial waves induced by spin-up of two immiscible fluid layers

Abstract: Interfacial waves of two immiscible layers in a spin-up container were investigated using experimental visualization. While the interface near the central part rose up, instability waves propagated in an azimuthal direction on the interface. These waves were mainly caused by Kelvin-Helmholtz instability for the velocity difference between two layers during spin-up, but had complicated transient characteristics owing to the rotation in a closed system. We visualized the structure of the interfacial waves by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The interfacial flow is strongly influenced by centrifugal acceleration, and the interfacial flow alters the ambient flows. This two-way interaction appears stronger for small density differences and large viscosity differences between the two fluids [46]. What is still lacking is a nonlinear numerical investigation of two immiscible fluids with strong sustained shear across the interface.…”
mentioning
confidence: 99%
“…The interfacial flow is strongly influenced by centrifugal acceleration, and the interfacial flow alters the ambient flows. This two-way interaction appears stronger for small density differences and large viscosity differences between the two fluids [46]. What is still lacking is a nonlinear numerical investigation of two immiscible fluids with strong sustained shear across the interface.…”
mentioning
confidence: 99%
“…A major feature of the density-stratified liquids sloshing is the presence of interfacial wave due to the density difference, which has seldom been studied [17][18][19]. Chang et al [20] studied the internal interfacial waves between two layers of liquids with different densities in a cylindrical container under vertical periodic excitation and found that the internal interfacial wave mode becomes more and more complicated as the density ratio of the upper and lower liquid layers increases.…”
Section: Introductionmentioning
confidence: 99%